St. Thomas Aquinas on God as Ipsum Esse Subsistens - Joseph G. Trabbic (Religions)
St. Thomas Aquinas’s doctrine of God as ipsum esse subsistens is not easy to understand. Even some of his more informed interpreters appear to struggle with it. In this paper, I attempt to explain the doctrine in a way that I hope is intelligible to a fairly broad philosophical audience. I also respond to Norman Kretzmann’s interpretation of it, which I think is mistaken. The main problem with Kretzmann’s interpretation seems to be a failure to grasp what Thomas means by esse.